2022
DOI: 10.3390/cells11121978
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death-1/Programmed Cell Death-1 Ligand as Prognostic Markers of Coronavirus Disease 2019 Severity

Abstract: Current research proves that immune dysregulation is a common feature of coronavirus disease 2019 (COVID-19), and immune exhaustion is associated with increased disease mortality. Immune checkpoint molecules, including the programmed cell death-1 (PD-1)/PD-1 ligand (PD-L1) axis, may serve as markers of disease severity. Accordingly, in this study, we evaluated the expression of PD-1/PD-L1 in patients with COVID-19. Blood immunophenotypes of hospitalized patients with moderate (n = 17, requiring oxygen support)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ]. Vulnerable patients with lower antibody titers or negative humoral response are the highest risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ]. Vulnerable patients with lower antibody titers or negative humoral response are the highest risk group.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study performed by Niedzwiedzka-Rystwej et al investigated the dynamic evolution of T, B, and NK cells during 14 days of hospitalization, both ICU and non-ICU, and the role of PD-1/PD-L1 as a biomarker for COVID-19 severity in hospitalized patients. They found that for the admission moment, the expression of PD-1/PD-L1 was higher for CD4 + and CD19 + cells, but not for CD8 + cells, and did not change during the study period [ 16 ], although the study did not provide the PD-1 expression on NK cells. In our study, the PD-1 expression was evenly distributed across the different time moments and disease outcomes for all NK subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors reported no difference in NK percentage between ICU and non-ICU patients, for all three time points, but NK cells were significantly higher in healthy controls compared to COVID-19 patients. Additionally, the NK population was found significantly higher in patients with fatal outcomes compared to survivors, and the percentage did not differ significantly across the moments [ 16 ]. In our study, the total NK % was slightly higher in survivors (not statistically significant), and for both fatal and non-fatal outcomes, the dynamic changes across the moments follow the same trend: higher NK percentage on admission with subsequent reduction of percentage during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the T cells reactivation by checkpoint inhibitors could represent a valid approach to counter COVID-19 infection [ 75 ]. Moreover, a PD-1 upregulation in CD4+ and CD8+ T cells was observed in COVID-19 disease, supporting the use of checkpoint inhibitors in reinforcing viral clearance [ 76 ]. The COPERNICO trial investigated the ability of Pembrolizumab (anti-PD-1 antibody) plus tocilizumab in interrupting hyperinflammation and restoring cellular immunocompetence ( Table 1 ).…”
Section: Therapeutic Agents In Clinical Trialsmentioning
confidence: 98%